Conversion of Biomass to Activated Carbon: A Synthesis Approach - Ashish Baldania; Bhalchandra Vibhute; Sachin Parikh (Current Innovations in Chemical and Materials Sciences Vol. 3, 2023)
The distinctive and versatile nature of activated carbon as an adsorbent lies in its extensive surface area and finely pored structure, leading to a remarkable adsorption capacity and reactivity. It can incorporate a variety of substances, with commonly utilized precursors for commercial production, including coconut shells and coal types like peat and lignite, each with its own structural and carbonic distinctions. Pinewood, owing to its abundant carbon content, is particularly prized as a source for generating highly porous activated carbon. Ongoing research into cost-effective and powerful adsorbents will contribute to environmental durability and offer advantageous outcomes for commercial interests in future scenarios. Through pyrolysis conducted under vacuum and without oxygen, the surface area is maximized, yielding an interlinked porosity. Waste biomass, being an economic resource, is effectively transformed into activated carbon with an impressive surface area of 969.075 m2/g.